Internet-based survey evaluating the impact of ground substrate on injury and performance in canine agility athletes - Jimenez, Isabel A.; Canapp, Sherman O.; Percival, Monica L. (Frontiers in Veterinary Science, 2022)
Agility is a rapidly growing canine performance sport worldwide, yet the literature is sparse regarding the impact of ground substrate on performance and injury. Approximately 1/3 of dogs participating in agility trials will experience a performance-related injury. The impact of ground material has been well-documented in racing greyhounds, equine athletes, and humans, but has been minimally investigated in agility dogs. In this retrospective, cross-sectional study, 300 respondents (handlers, owners, and trainers) of 308 agility dogs completed an online survey regarding their dog’s training and competition regimen, history of injury, perceived association between injury and substrate and/or agility obstacle, markers of decreased performance (MDPs) observed on different substrates, and changes to routine following injury. 35.7% of dogs sustained a training injury (TI) and 11.2% sustained a competition injury (CI). The most commonly reported sites of injury were the shoulder (TI: 33.9%, CI: 25.4%), forelimb digits (TI: 14.7%, CI: 11.9%) and iliopsoas muscle (TI: 11.9%, CI: 13.6%). Dogs most commonly trained on natural grass (85.3%), artificial turf (50.8%), and dirt (34.5%). Significantly fewer MDPs were observed on natural grass than any other substrate except dirt. Significantly more MDPs were noted on rubber mat compared to natural grass, artificial turf, dirt, sand, or foam mat. Rubber mat had the highest Incidence Proportion (IP) (32.0%) of TI and was perceived to be related to TI in 87.5% of cases. Obstacles perceived to be associated with injuries included jumps (TI: 37.5%, CI: 27.8%), contacts (TI: 29.7%, CI: 22.2%), weaves (TI: 11.9%, CI: 13.9%), and tunnels (CI: 25.0%). Overall, agility dogs were perceived to perform best on natural grass and dirt, while rubber mat was associated with injury and decreased performance. Respondents were willing to make significant alterations to their dog’s routine due to a perceived association between substrate, injury, and performance. Further prospective studies are needed to assess the impact of substrate composition and maintenance, and inform evidence-based recommendations to maximize performance and minimize performance-related injury in agility dogs.